2019
DOI: 10.1039/c9nr06831g
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity suppression in GaAs–AlAs core–shell nanowire arrays

Abstract: Semiconductor nanowire heterostructures have been shown to provide appealing properties for optoelectronics and solid-state energy harvesting by thermoelectrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In addition to the n-type InAs system studied here, this would allow the investigation of both p-type materials required by complementary thermoelectric generators and higher-performing n-type materials, such as InSb, which has previously been predicted to possess the highest thermoelectric power factor among the III-V compounds . Further, introducing core–shell heterostructures could offer a pathway to increased control over both the electronic and thermal transport in the network structure …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the n-type InAs system studied here, this would allow the investigation of both p-type materials required by complementary thermoelectric generators and higher-performing n-type materials, such as InSb, which has previously been predicted to possess the highest thermoelectric power factor among the III-V compounds . Further, introducing core–shell heterostructures could offer a pathway to increased control over both the electronic and thermal transport in the network structure …”
Section: Resultsmentioning
confidence: 99%
“…11 Further, introducing core−shell heterostructures could offer a pathway to increased control over both the electronic and thermal transport in the network structure. 50…”
Section: Resultsmentioning
confidence: 99%
“…114 Several experimental and theoretical studies have shown the possibilities of producing promising thermoelectric materials in the form of core-shell nanowires. [115][116][117][118] Successful examples include Ge@Si, 114,115,119,120 Si@Ge, 121,122 GaAs@AlAs, 117 GaAs@AlGaAs, 123 Bi 2 S 3 @Bi, 116 Bi@Te, 124 Te@Bi, 125 Bi@TiO 2 , 126 multiwalled carbon nanotubes (MWCNT)@Sb 2 Te 3 , 127 Bi 2 Te 3 @MWCNT, 128 and so on. These special heterostructures show superior electronic properties and a significant reduction in thermal conductivity compared to single element nanowires.…”
Section: Core-shell Nanostructures As Building Blocksmentioning
confidence: 99%
“…For example, a strong thermal conductivity reduction was found in Si and SiGe alloy NWs with diameters of few tens of nanometers, indicating the important effect of the core-shell interface on phonon transport [54]. Juntunen et al also found up to~60% reduction of the thermal conductivity of GaAs NWs coated with AlAs shells [55]. A different study showed that the k along a single Si nanowire can be tuned (between crystalline and amorphous limits) through selective helium ion irradiation with a well-controlled dose [56].…”
Section: Nanowiresmentioning
confidence: 99%